Cryopreserved or fresh mesenchymal stromal cells: only a matter of taste or key to unleash the full clinical potential of MSC therapy? - Moll, Guido; Bieback, Karen (Biobanking and cryopreservation of stem cells, 2016)
Mesenchymal stromal cells (MSCs) harbor great therapeutic potential for numerous diseases. From early clinical trials, success and failure analysis, bench-to-bedside and back-to-bench approaches, there has been a great gain in knowledge, still leaving a number of questions to be answered regarding optimal manufacturing and quality of MSCs for clinical application. For treatment of many acute indications, cryobanking may remain a prerequisite, but great uncertainty exists considering the therapeutic value of freshly thawed (thawed) and continuously cultured (fresh) MSCs. The field has seen an explosion of new literature lately, outlining the relevance of the topic. MSCs appear to have compromised immunomodulatory activity directly after thawing for clinical application. This may provide a possible explanation for failure of early clinical trials. It is not clear if and how quickly MSCs recover their full therapeutic activity, and if the “cryo stun effect” is relevant for clinical success. Here, we will share our latest insights into the relevance of these observations for clinical practice that will be discussed in the context of the published literature. We argue that the differences of fresh and thawed MSCs are limited but significant. A key issue in evaluating potency differences is the time point of analysis after thawing. To date, prospective double-blinded randomized clinical studies to evaluate potency of both products are lacking, although recent progress was made with preclinical assessment. We suggest refocusing therapeutic MSC development on potency and safety assays with close resemblance of the clinical reality.
Gesehen am 13.02.2019
First Online 12 November 2016